2006
DOI: 10.1007/s10722-004-0981-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Wild Common Beans from Northwestern Argentina Based on Morpho-agronomic and RAPD Data

Abstract: The genetic diversity among 10 wild populations of common bean Phaseolus vulgaris var. aborigineus was analyzed by means of RAPD markers and morpho-agronomic data. The study was performed on populations collected from different sites located in the provinces of Jujuy, Salta and Tucuma´n in northwestern Argentina. Ten quantitative traits and 33 random primers were scored. Clustering based on morpho-agronomic traits and RAPD markers generated similar phenograms that grouped bean populations based on their site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
4
16
1
2
Order By: Relevance
“…The genetic distance matrix showed that the AGD within the wild type accessions was higher than the AGD within P. augusti, within the Mesoamerican gene pool or within the Andean gene pool and was similar to the AGD among the wild versus cultivated Andean beans. These results suggest wide genetic variability in the wild accessions of P. vulgaris in Bolivia and are in contrast with previous studies with wild Andean populations of common bean from north-western Argentina (Galván et al, 2006), which were more limited in diversity.…”
Section: Discussioncontrasting
confidence: 99%
“…The genetic distance matrix showed that the AGD within the wild type accessions was higher than the AGD within P. augusti, within the Mesoamerican gene pool or within the Andean gene pool and was similar to the AGD among the wild versus cultivated Andean beans. These results suggest wide genetic variability in the wild accessions of P. vulgaris in Bolivia and are in contrast with previous studies with wild Andean populations of common bean from north-western Argentina (Galván et al, 2006), which were more limited in diversity.…”
Section: Discussioncontrasting
confidence: 99%
“…Some researchers have suggested that the use of morphological traits should be complemented with more accurate techniques to achieve reliable evaluation and characterisation of species diversity (Escribano et al 1997;galvan et al 2006). Further, in recent years successful results could be obtained using DNA markers and molecular techniques for determination of genetic traits for bean improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in recent years successful results could be obtained using DNA markers and molecular techniques for determination of genetic traits for bean improvement. Tohme et al (1996), Alvarez et al (1998), Sicard et al (2005), and Galvan et al (2006) analysed diversity among common beans by molecular tools.…”
Section: Discussionmentioning
confidence: 99%
“…In common bean, genetic diversity has been evaluated in the past using both morphological and molecular markers (Galvan et al 2006). Among molecular markers, microsatellites are one of the most popular genetic markers due to their characteristic features like high polymorphism, abundant informativeness, convenience of assay by PCR, and distribution throughout the genome (Gupta and Varshney 2000).…”
Section: Introductionmentioning
confidence: 99%